K9HeartCircDB: a circRNA atlas of tachypacing-induced canine dilated cardiomyopathy - Chinmaya Chinmaya; Tanvi Sinha; Noemi Nisini; Tao Wang; Natarajaseenivasan Suriya Muthukumaran; Rishi Dhanasekaran; Remus Berretta; Amit Kumar Rai; Amaresh Chandra Panda; John W. Elrod; Raj Kishore; Steven R. Houser; et al. (Journal of Translational Medicine, 2026)
Abstract Background Cardiovascular disease (CVD) remains a leading cause of mortality worldwide. Dilated cardiomyopathy (DCM), a major contributor to heart failure (HF), is characterized by ventricular dilation, impaired systolic and diastolic function, arrhythmias, and adverse cardiac remodeling. While genetic causes of DCM have been extensively investigated, non-genetic and acquired forms of DCM-like HF remain less well understood, particularly regarding regulation by non-coding RNAs. Circular RNAs (circRNAs) are stable, covalently closed RNAs that regulate cellular processes through interactions with microRNAs, RNA-binding proteins, and translational machinery; however, their role in non-genetic DCM-like HF is largely unexplored. Methods We developed K9HeartCircDB ( https://www.k9heartcircdb.com/ ), a publicly accessible database of circRNAs identified in canine left ventricular (LV) tissues. The dataset includes samples from tachypacing-induced HF, a model of non-genetic DCM-like disease, and healthy controls. CircRNAs were annotated and integrated into a user-friendly platform that enables queries based on exon composition, predicted microRNA binding sites, protein-coding potential, siRNA targets, and primer design for validation. Results K9HeartCircDB provides a comprehensive catalog of circRNAs expressed in canine LV tissues under both HF and control conditions. The platform offers multiple analytical features, including circRNA annotation, predicted regulatory interactions, and experimental design support. Comparative exploration of circRNA profiles between tachypacing-induced HF and normal tissues enables identification of candidate molecules associated with non-genetic DCM-like pathology. Conclusions K9HeartCircDB represents an integrated and accessible resource for studying circRNA biology in canine HF. By facilitating exploration of circRNA expression and function in a translationally relevant large-animal model, this database supports mechanistic investigations and advances research into non-genetic DCM-like disease.